Maintaining channel abandonment processes increases riparian plant diversity within fluvial corridors. Issue 5 (4th September 2014) - Dufour, Simon; Hayden, Maya; Stella, John; Battles, John; Piegay, Herve; Boudell, Jere A.; Dixon, Mark D.; Rood, Stewart B.; Stromberg, Juliet C.
Abstract Within dynamic alluvial riverine corridors, abandoned channels form and experience hydrogeomorphic processes that are distinct from similar elevation surfaces along active channels. Compared with the relatively well‐studied role of fluvial disturbance on floodplain plant communities along active channels, the drivers of plant diversity and community dynamics along terrestrializing abandoned channels have received much less attention. In this study, we addressed several related questions within the context of the Sacramento River (California, USA): (1) Do abandoned channels host different plant species compared with the surrounding floodplain? (2) How do plant communities vary among abandoned channels in relation to time since cutoff and disturbance regime? (3) Do understory plant species within an abandoned channel display distinct zonation along a disturbance gradient from the wetted edge laterally to upland areas? Our results show that although species richness is similar to floodplain sites, abandoned channels support a different species pool, notably due to presence of more wetland‐associated species, and this contributes to increase biodiversity within the fluvial corridor. We found substantial shifts in species composition that occurred since channel abandonment, likely related to decreases in the strength of hydromorphic disturbance through time. Lastly, we found that lateral environmental gradients within abandoned channel sites were significant, although much weaker drivers of understory vegetation patterns than typically found along active channel banks. These results argue for a management approach that preserves and promotes natural processes of channel migration and sediment dynamics. Copyright © 2014 John Wiley & Sons, Ltd.